Wavelength‐Gated Photochemical Synthesis of Phenalene Diimides. Issue 18 (18th March 2021) - Feist, Florian; Walden, Sarah L.; Alves, Jessica; Kunz, Susanna V.; Micallef, Aaron S.; Brock, Aidan J.; McMurtrie, John C.; Weil, Tanja; Blinco, James P.; Barner‐Kowollik, Christopher
Abstract: Herein, we pioneer a wavelength‐gated synthesis route to phenalene diimides. Consecutive Diels–Alder reactions of methylisophthalaldehydes and maleimides afford hexahydro‐phenalene‐1, 6‐diol diimides via 5‐formyl‐hexahydro‐benzo[f]isoindoles as the intermediate. Both photoreactions are efficient (82–99 % yield) and exhibit excellent diastereoselectivity (62–98 % d.r.). The wavelength‐gated nature of the stepwise reaction enables the modular construction of phenalene diimide scaffolds by choice of substrate and wavelength. Importantly, this synthetic methodology opens a facile avenue to a new class of persistent phenalenyl diimide neutral radicals, constituting a versatile route to spin‐active molecules. Abstract : Methylisophthalaldehydes form two highly reactive ortho ‐quinodimethane dienophiles in a step‐wise and wavelength gated fashion. Trapping with maleimides proceeds with high stereoselectivity under the formation of phenalene diimide scaffolds. Subsequent elimination and oxidation affords a new class of persistent phenalenyl diimide neutral radicals.